Erasmus Program and Labor Market Outcomes: Evidence from a Fuzzy Regression Discontinuity Design - Marco Alberto De Benedetto; Maria De Paola; Vincenzo Scoppa; Janna Smirnova (Institute of Labor Economics (IZA), 2023)
We study the impact that participation in the Erasmus program produces on a number of labor market outcomes. By implementing a Fuzzy Regression Discontinuity Design, we show that participating in the international mobility program positively affects the probability of being employed three years after graduation and reduces the time spent to find a job, whereas no significant effect is found on the likelihood of getting a job in line with the qualification acquired. These results are mainly driven by male and STEM graduates. We further investigate potential mechanisms underlying our results and find that spending a period of time studying abroad improves both the proficiency in spoken English and graduates' academic performance, and tends to increase the willingness to move to find a job.
Keywords: C26; D04; I23; I26; J00; 330; international mobility; Erasmus; academic outcomes; employment; Fuzzy Regression Discontinuity Design